Pengaruh Latihan SAQ Terhadap Kecepatan Dan Kelincahan Pada Siswa Ekstrakurikuler Futsal SMKN 2 Selong Tahun Pelajaran 2019/2020 - Pauzul Latip; Isyani Isyani (UNIVERSITAS NEGERI MAKASSSAR, 2020)
ABSTRACTBased on observations on futsal players at SMKN 2 Selong, there are still many players who are not fast and agile when carrying out attacks or when defending. Players are still slow to counterattack to take advantage of opportunities to score goals. This is evidenced by several tournaments that were attended by SMKN 2 Selong players, individual mistakes made by players when attacking or defending, resulting in opponents easily reading the game of SMKN 2 Selong. This study aims to determine the effect of SAQ training on speed and agility in futsal extracurricular students at SMKN 2 Selong in the 2019/2020 academic year. This research uses experimental research. This study used three variables consisting of one independent variable (SAQ exercise) and two dependent variables, namely speed and agility in futsal extracurricular students at SMKN 2 Selong in the 2019/2020 academic year. The population used in this study were 20 extracurricular futsal students at SMKN 2 Selong for the 2019/2020 academic year, which were divided into two groups, namely group I, namely the group using SAQ training on speed and group II, namely the group using SAQ training on agility. As for the distribution of the sample by using a random system or shaking the arisan, it is usually called simple random sampling. The data analysis technique used in this study was the Group Pretest-Posttest Design. The research results from data analysis using T-test analysis with a significant level of 5%. The results of this study indicate that (1) There is an effect of SAQ training on speed in futsal extracurricular activities at SMKN 2 Selong in the 2019/2020 academic year and (2) There is an effect of SAQ training on speed in futsal extracurricular activities at SMKN 2 Selong for the 2019/2020 academic year